Faktor Risiko Diabetes Mellitus Tipe 2 - Fatma Nuraisyah (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2017)
Type II Diabetes Mellitus (DM) was not infectious and prevalence multifactorial to increased on Indonesia. It was the fourth largest in the world of type II DM.People awareness was about type II DM needed to can help prevent the incidence increased incidence and prevalence it. Objective to identify risk factors type II DM associated with outpatients at Panjatan II Public Health Center. Method Cross sectional study was conducted on 82 outpatient of Public Health Panjatan II. We used purposive sampling with spesific clasification criterias. Data collection were characteristic physical test and laboratory test. family history and age were significantly to outpatients with type II DM.